Preventing the building turbo from turning into a corruption turbo: Why landownership transparency is now essential - Hartmann, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2026)
The German law for „Accelerating Housing Construction and Securing Housing“ – the so-called Bauturbo – fundamentally changes key mechanisms of democratic control in the German planning system. The new provisions, especially the new possibility of extensive deviations from the Federal Building Code (§246e BauGB) combined with the regulation on „presumption of municipal consent“ (§36a BauGB) shift decision-making processes from democratically legitimized planning procedures toward simplified administrative acts. This change creates broader discretionary powers, information and power asymmetries between public authorities and private actors and increasing intransparency in land policy. These structural changes may foster corruption by enabling hidden influences on land value increases. The risk arises less from individual misconduct than from the systemic incentives generated by the Bauturbo itself. This paper highlights these risks and serves as a basis for discussion on how to mitigate them. Strengthening transparency of land ownership is proposed as a key approach to reinforce the legitimacy of planning law and restore trust in fair and accountable development processes.